Categories of Aspect and State in the Process of Learning Ukrainian as a Foreign Language. - Труба, А. Н. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
The article is devoted to considering the issue concerning the interaction of state and aspect categories in broad and narrow senses. The notions and functions of an aspect category implemented in verbal nouns have been considered; functions and signs of a state category have been defined. The issue concerning grammar representation of this interaction has been considered and the frequency of this general segment usage has been determined.